Evaluating the science book for the sixth grade according to NGSS standards for the next generation - Ahmed Ammar Jawad; Alaa Ahmed Abdel Wahid (Zanco Journal of Humanity Sciences)
The goal of the current research is to evaluate the science book for the sixth grade of elementary school, which is decided by the Iraqi Ministry of Education according to the science standards for the next generation (NGSS). To achieve this goal, the researchers prepared a list of three dimensions: scientific and engineering practices, comprehensive concepts and basic ideas. The basic ideas included four areas: life sciences, physics and science Earth, space, engineering and technology, and twenty-seven standards and indicators for standards, numbering (154) indicators, which included examples of criteria indicators, then the two researchers analyzed the content of the science book for the sixth primary scheduled for the academic year (2018-2019) in light of this criterion with a total of 247 pages analyzed The two researchers adopted the explicit and implicit idea in the analysis and gave an evaluation description of the unfulfilled standards in the book with activities, examples and questions related to the content of the science book for the sixth grade. The two researchers reached conclusions that the science textbook for the sixth grade of elementary school achieved a percentage of (59.86%), and this percentage is considered medium compared to the ratios adopted by the researchers, as the book achieved (91) paragraphs out of (152) paragraphs.